The first Islamic psychology summit resolutions - Rahman, Shukran Abdul (International Association of Muslim Unity, 2025)
The first Islamic Psychology Summit brought together scholars, researchers, and practitioners to explore and discuss the theme “Redefining Psychology: The Transformative Power of Islamic Principles in Elevating Human Dignity.” The Summit organized by the International Association of Muslim Psychologists (IAMP) and Universitas Gadjah Mada, Indonesia, has manifested the commitment of various parties to contributing to the development of Islamic Psychology. This Summit urges a collective responsibility to redefine psychology through Islamic principles, fostering a discipline that recognizes the totality of human experience and the importance of spiritual, mental, and physical healt